PENGGUNAAN BIOURIN SAPI TERHADAP KUALITAS HASIL BAYAM MERAH (Amaranthus tricolor L.) - Sutoyo, Sutoyo; Sumiati, Astri; Hakim, Lukmanul (BUANA SAINS, 2025)
The decline in red spinach (Amaranthus tricolor L.) production in Indonesia has prompted the need to explore effective and environmentally friendly alternatives to conventional fertilizers. This study examines the potential of cow biourine as a liquid organic fertilizer to increase the yield and nutritional quality of red spinach. The field experiment used a Randomized Block Design with five levels of biourine concentration (0, 200, 400, 600, 800 ml). The variables measured included growth components (fresh weight and productivity) and quality (protein and calcium content). The analysis results showed that the application of cow biourine significantly increased fresh weight, productivity, and calcium content. A dose of 400 ml proved to be the optimal treatment with a wet weight of 120.16 g, a productivity of 4.71 tons/ha, and a calcium content of 469.83 ppm.